Efektivitas Bahan Ajar Buku Panduan Pembelajaran Kebencanaan Kabupaten Klaten Pada Bencana Letusan Gunung Berapi Melalui Strategi Jigsaw di SMA Negeri 2 Klaten - Prabowo, Astrid Dery, Drs. Dahroni, M.Si (2016)
State Senior High School 2 Klaten is located at Jalan Angsana, and located in the Gadingan hamlet, Trunuh Village, District of South Klaten, Klaten regency. The method used in the study is experimental while the design of the study is a pretestposttest control group design, with a population of class X as many as 70 students are divided into two classes, namely class X MIPA 5 is an experimental class in learning to use strategies jigsaw while class X MIPA 3 is control class in learning using conventional methods. The study concluded that (1) based on the Mann-Whitney test known significant value 0.004 <0.05, it can be concluded there was significant difference between the experimental class and control class (2) an increase learning goals using teaching materials on disaster learning guide books Klaten district in experimental class showed an increase learning goals seen from the pre-test by 42 increased to 34.66 or 76.66 adrift margin increased by 82.54%. while the control class when viewed from the pre-test showed the results of 43.42 risen to 65, 71 on the value of post test adrift difference 22.28, or increase of 51.3%. Then the average value of student learning goals experimental class is higher when compared than the control class. Keywords: Jigsaw strategy, improvement of educational goals, teaching materials.